Combining time and position dependent effects on a single machine subject to rate-modifying activities - Rustogi, Kabir; Strusevich, Vitaly A. (Omega (Oxford), 2014)
We introduce a general model for single machine scheduling problems, in which the actual processing times of jobs are subject to a combination of positional and time-dependent effects, that are job-independent but additionally depend on certain activities that modify the processing rate of the machine, such as, maintenance. We focus on minimizing two classical objectives: the makespan and the sum of the completion times. The traditional classification accepted in this area of scheduling is based on the distinction between the learning and deterioration effects on one hand, and between the positional effects and the start-time dependent effects on the other hand. Our results show that in the framework of the introduced model such a classification is not necessary, as long as the effects are job-independent. The model introduced in this paper covers most of the previously known models. The solution algorithms are developed within the same general framework and their running times are no worse than those available earlier for problems with less general effects. •We study enhanced scheduling models with combined job-independent effects.•Models combine learning and deterioration and positional and time-dependent effects.•The machine undergoes rate-modifying activities that split the jobs into groups.•The effects incorporate group-dependence.•Single machine scheduling problems in such settings are solvable in polynomial time.